Between the Local and the Global: Interwining Archives for the Construction of the History of Colonial Northeast Rioplatense (Glocalism: Journal of Culture, Politics and Innovation, 2021)
This research recovers methodological and heuristic interests that developed a few years ago, which have led us to work on the local and global historical archives from a humanistic horizon. This task puts us in a different place as historians, for it forces us to rethink the social function of the archives and of the historians in those archives. In the Northeast region of present-day Argentina, the space for discussion on archives begins to be a terrain won over by historians, who develop projects to recover, digitise and conserve documentary sources. Throughout this article we will focus on characterising a set of global and local archives that are vital to Rioplatense colonial history. We are interested in problematizing about documentary dispersion and how we build documentary corpus from sources that lie in different repositories. Beyond exploring them and briefly entering its institutional history, the work is oriented to present an in-depth analysis of the documentary typologies that can be found in those archives and that are vital to historical research in the region.
Keywords: archives; colonial history; repositories; globalisation; Río de la Plata